Preventing Stunting from Pregnancy through “Gosting” (Healthy Gohyong Anti-Stunting) - Intan Sri Sugiharlianti; Diana Damayanti (International Journal of Community Services, 2026)
Background: The prevalence of stunting in 2024 in the working area of the Kalapa Nunggal Sukabumi Health Center UPTD was 172 (4.98%). From a preliminary survey conducted randomly among pregnant women, it was found that some pregnant women still did not know about stunting prevention in children during pregnancy. The provision of PMT has reduced the incidence of stunting every year. Objective: This activity aims to increase the knowledge of pregnant women about stunting prevention, starting from pregnancy or the First 1000 Days of Life. Method: Participants in this activity were 15 pregnant women and Posyandu cadres. The activity began with a preliminary survey, a Forum Group Discussion (FGD) to determine problem priorities and implement interventions. The intervention was carried out by providing counseling and a Gohyong menu demonstration. Results: The results of the activity showed that direct education was very effective in increasing their knowledge and awareness about stunting. Before the activity was carried out, generally, participants did not clearly understand what stunting is, its causes, or how to prevent it. However, through a communicative approach and easy-to-understand delivery, participants became more aware of the importance of nutritional intake during pregnancy. Conclusion: The health education successfully increased pregnant women's understanding of the importance of balanced nutrition and a healthy lifestyle in preventing stunting during pregnancy. The introduction of healthy menus such as healthy gohyong also strengthened participants' understanding of the daily implementation of balanced nutrition, thus encouraging healthier behavior changes.